Meshing Characteristics Analysis of a High-speed-ratio Compound Gear with Small Tooth Difference - Zhu Feihong; Song Chaosheng; Chang Le; Lü Zhenyu; Du Xuesong; Huang Yucheng (Jixie chuandong)
This study analyzes the transmission principle and structural characteristics of a high-speed-ratio compound gear with small tooth difference. On this basis, the finite element meshing characteristic analysis model of the above gear transmission device is established. The model considers the coupling deformation of 3-stage transmission, the specific structure of the cycloid gear, the output disc, the planet carrier and the case. The stress of each key component and the transmission error of the whole machine are simulated and analyzed, and the dynamic process of the multi-tooth meshing of the pin-cycloid transmission is discussed in detail. The results show that during the operation of the reducer, the stress fluctuation range of each component is small, and they are all far below the yield limit of their materials. The two cycloidal gears always bear the load through a rigid zone and a flexible zone simultaneously. The teeth of the rigid zone are the main bearing zone, and the teeth of the flexible zone are less stressed. The total number of meshing gear teeth of the two cycloidal gears is 9-11. The transmission error curve is stable and periodic, without noticeable long waves, and the peak-to-peak value of the transmission error of the whole machine is 46.719 5″. This research provides a theoretical basis for the optimal design of dynamic characteristics and meshing characteristics of the high-speed-ratio compound gear with small tooth difference.